Baseline SCAT Performance in Men and Women: Comparison of Baseline Concussion Screens Between 6288 Elite Men's and 764 Women's Rugby Players. Issue 6 (November 2021) - Tucker, Ross; Falvey, Eanna; Fuller, Gordon; Brown, James; Raftery, Martin
Abstract : Objective: This study compared Sports Concussion Assessment Tool (SCAT) performance in elite male (6288 players) and female (764 players) rugby players, to determine whether reference limits used for the management and diagnosis of concussion should differ between sexes. Design: Cross-sectional census sample. Setting: Data from World Rugby's Head Injury Assessment management system were analyzed. This data set covers global professional rugby. Participants: All professional players who underwent baseline SCAT testing as part of World Rugby's concussion management requirement formed the study cohort. Ten thousand seven hundred fifty-four SCAT assessments from 6288 elite male rugby players and 1071 assessments from 764 elite female players were analyzed. Intervention: Elite men and women rugby players are independent variables. Main Outcome Measures: Sports Concussion Assessment Tool performance, including symptoms endorsed, cognitive submode performance, and balance performance. Results: Women endorsed significantly more symptoms, with greater symptom severity, than men (relative ratio 1.34, 95% confidence interval, 1.25-1.45 women vs men). Women outperformed men in cognitive submodes with the exception of immediate memory and delayed recall and made fewer balance errors than men during the modified Balance Error Scoring System. Clinical reference limits, defined as submode score achieved by the worst-performing 50% of the cohort, did not differ between men and women. Conclusions: Women and men perform differently during SCAT baseline testing, although differences are small and do not affect either the baseline or clinical reference limits that identify abnormal test results for most submodes. The greater endorsement of symptoms by women suggests increased risk of adverse concussion outcomes and highlights the importance of accurate evaluation of any symptom endorsement at baseline.